Analysis of Tourist Satisfaction with Halal Tourism in Aceh - Desky, Harjoni; Thaver, Beverly; Rijal, Syamsul (UIN Sunan Gunung Djati Bandung, 2022)
Halal tourism has now become a sector that can influence an important role in the economic development of a nation. The purpose of this study is first, to find out how the influence of halal tourism on tourist satisfaction; and second, knowing the satisfaction of tourists visiting Banda Aceh City. The method used in this research is a quantitative method, through a field research approach (field research) is studied to answer the existing hypotheses, the data is analyzed by validity testing, reliability testing, and simple regression testing (t test) using the SPSS 20.0 application. The results shows there is an influence of halal tourism on the satisfaction of tourists visiting the city of Banda Aceh. This is proved by several assessments which are given by tourists (respondents) who have visited Banda Aceh City in 2018. In addition, the regression results show that the t count > t table, where the t count value is 8.205 while the t table value is 0.201. It shows that null hypothesis (H0) is rejected and alternative hypothesis (HI) is accepted. It means that there is a significant influence between halal tourism on tourist satisfaction. The coefficient of R Square shows the magnitude of halal tourism effect on tourist satisfaction in Banda Aceh City, with the value of R Square is 0.584. It means that the magnitude of the influence of halal tourism on tourist satisfaction in Banda Aceh City is 58.4 percent and the remaining 41.6 percent is influenced by other factors that are not examined by researchers.